CHRONIC DISEASE AND HEALTH EDUCATION: TRAINING CHALLENGES FOR GENDER-SENSITIVE CARE - Izabel Pezarini Jiacon, Milene; Barreto Pereira, Jéssica; Cristina Vieira da Silva, Viviane; Alves dos Santos, Suenny; Fabíola Silva Araújo, Mayonara; Andreza de Arruda, Marília; Nelson Martins Júnior, Leonidas (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to discuss the training challenges faced by healthcare professionals in the care of people with chronic diseases, with an emphasis on promoting gender-sensitive educational practices. Based on a narrative literature review, studies published between 2023 and 2025 that address the interface between health education, professional training, social vulnerabilities, and care strategies in different territories were analyzed. The analysis highlighted two central categories: the need for critical and intersectional training, and the role of community spaces and digital technologies in mediating care. The results indicate that educational actions continue to be anchored in biomedical models, often disregarding gender inequalities and the sociocultural realities of those receiving care. Initiatives based on dialogue, listening, and valuing popular knowledge, as well as the use of media such as podcasts and discussion groups, proved effective in promoting autonomy and adherence to treatment. It is concluded that educational practices that incorporate intersectional and community perspectives are fundamental to building comprehensive, fair, and welcoming care for people with chronic diseases.